Stages of Community-Based Social Rehabilitation Services for Children with Disabilities in Cibiru Wetan Village Bandung - Muktiwibowo, Adityo; Prayogi, Arditya (SocioHumania: Journal of Social Humanities Studies, 2024)
Community social workers have an important role in providing social rehabilitation services in the community, especially for children with disabilities. Community social workers work with the community, mobilizing and sensitizing the community to jointly take action in dealing with the problems of children with disabilities. Thus, this article aims to provide knowledge and understanding of the stages of activities carried out by community social workers in community-based social rehabilitation services for children with disabilities in Cibiru Wetan village, Bandung. This article was prepared and analyzed using a qualitative approach supported by data collection techniques in the form of interviews, observation and documentation. From the results of the study, it is clear that there are fourteen stages carried out by social workers in providing community-based social rehabilitation services for children with disabilities in Cibiru Wetan village, Bandung. This activity begins with increasing the role and support of the community and ends with the stage of making a report.